The Impact of Oat Quality on White Salted Noodles Containing Oat Flour. Issue 3 (23rd November 2015) - Mitra, Sabori; James, Anthony Paul; Fenton, Haelee Kim; Cato, Larisa; Solah, Vicky Ann
Abstract : This research compared the physicochemical properties of six milling oat cultivars from Western Australia over two growing seasons (2011 and 2012). Variations among the cultivars in physicochemical properties, particularly β‐glucan content, were assessed to determine their suitability for incorporation into white salted noodles at a level of 30% of the flour component. The average across six oat cultivars grown in 2012 was significantly higher ( P < 0.05) for protein content, lipid content, and volume of smaller sized particles (<100 µm) and significantly lower for ash content, starch damage, and volume of larger particles (>100 µm) in comparison with the average across the same oat cultivars grown in 2011. The year of cultivation by cultivar interaction was significant ( P < 0.05) for ash content, protein content, β‐glucan content, starch damage, and particle size. Oat cultivar Mitika had the highest peak viscosity for 100% oat flour (whole groat) and 30% oat–wheat (OW) flour blend, which may be owing to lower amylose percentage, high protein content, and greater volume of smaller particles. The effect of growing season had greater impact on OW noodle firmness than the genetic effect of cultivars. The eating and cooking quality attributes of OW noodles, such as color, color stability, firmness, and cooking solid loss were superior for those incorporated with 2012 oat flour (whole groat) compared with 2011 oat flour. Among the six oat cultivars, Williams produced noodles with poor cooking and eating quality, and Mitika was easier to handle during processing and produced noodles with superior brightness and color stability in comparison with other oat cultivars evaluated.